Roles and functions of SARS-CoV-2 proteins in host immune evasion - Rashid, Farooq; Xie, Zhixun; Suleman, Muhammad; Shah, Abdullah; Khan, Suliman; Luo, Sisi (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome virus 2 (SARS-CoV-2) evade host immune system. SARS-CoV-2 encodes sixteen non-structural, four structural and nine accessory proteins. Different proteins of this virus play indispensable roles to suppress the production and signaling of type I and III interferons. In this review, we mainly talk about functions and the underlying mechanisms of different proteins of SARS-CoV-2 to evade host immune system. We highlighted relatively well-studied SARS-CoV-2 proteins for their roles in suppression of IFNβ production, interferon regulatory factor 3 (IRF3) nuclear translocation, TANK binding kinase 1 (TBK1)/IRF3/ signal transducer and activator of transcription (STAT) 1 and STAT2 phosphorylation. The well-studied SARS-CoV-2 proteins are, Non-structural protein (NSP) 1, NSP6, NSP8, NSP12, NSP13, NSP14, NSP15, open reading frame (ORF) 3a, ORF6, ORF8, ORF9b, ORF10 and Membrane (M) protein. However, the detailed mechanism of immune evasion by NSP5, ORF3b, ORF9c and Nucleocapsid (N) proteins is lacking. We also elaborate the perspectives of SARS-CoV-2 proteins.